Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To determine which point lies on the circle represented by the equation [tex]\((x+7)^2 + (y-10)^2 = 13^2\)[/tex], we will plug each point into the circle's equation and check if the equation holds true.
### Analyzing Option A: [tex]\((5, 12)\)[/tex]
Substitute [tex]\( x = 5 \)[/tex] and [tex]\( y = 12 \)[/tex] into the equation:
[tex]\[ (5+7)^2 + (12-10)^2 = 13^2 \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ (12)^2 + (2)^2 = 169 \][/tex]
Now, calculate the squares:
[tex]\[ 144 + 4 = 148 \][/tex]
Since [tex]\( 148 \neq 169 \)[/tex], point [tex]\((5, 12)\)[/tex] does not lie on the circle.
### Analyzing Option B: [tex]\((-7, -3)\)[/tex]
Substitute [tex]\( x = -7 \)[/tex] and [tex]\( y = -3 \)[/tex] into the equation:
[tex]\[ (-7+7)^2 + (-3-10)^2 = 13^2 \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ (0)^2 + (-13)^2 = 169 \][/tex]
Now, calculate the squares:
[tex]\[ 0 + 169 = 169 \][/tex]
Since [tex]\( 169 = 169 \)[/tex], point [tex]\((-7, -3)\)[/tex] lies on the circle.
### Analyzing Option C: [tex]\((-6, -10)\)[/tex]
Substitute [tex]\( x = -6 \)[/tex] and [tex]\( y = -10 \)[/tex] into the equation:
[tex]\[ (-6+7)^2 + (-10-10)^2 = 13^2 \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ (1)^2 + (-20)^2 = 169 \][/tex]
Now, calculate the squares:
[tex]\[ 1 + 400 = 401 \][/tex]
Since [tex]\( 401 \neq 169 \)[/tex], point [tex]\((-6, -10)\)[/tex] does not lie on the circle.
### Analyzing Option D: [tex]\((6, 23)\)[/tex]
Substitute [tex]\( x = 6 \)[/tex] and [tex]\( y = 23 \)[/tex] into the equation:
[tex]\[ (6+7)^2 + (23-10)^2 = 13^2 \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ (13)^2 + (13)^2 = 169 \][/tex]
Now, calculate the squares:
[tex]\[ 169 + 169 = 338 \][/tex]
Since [tex]\( 338 \neq 169 \)[/tex], point [tex]\((6, 23)\)[/tex] does not lie on the circle.
### Conclusion:
The point that lies on the circle represented by the equation [tex]\((x+7)^2 + (y-10)^2 = 13^2\)[/tex] is:
B. [tex]\((-7, -3)\)[/tex]
### Analyzing Option A: [tex]\((5, 12)\)[/tex]
Substitute [tex]\( x = 5 \)[/tex] and [tex]\( y = 12 \)[/tex] into the equation:
[tex]\[ (5+7)^2 + (12-10)^2 = 13^2 \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ (12)^2 + (2)^2 = 169 \][/tex]
Now, calculate the squares:
[tex]\[ 144 + 4 = 148 \][/tex]
Since [tex]\( 148 \neq 169 \)[/tex], point [tex]\((5, 12)\)[/tex] does not lie on the circle.
### Analyzing Option B: [tex]\((-7, -3)\)[/tex]
Substitute [tex]\( x = -7 \)[/tex] and [tex]\( y = -3 \)[/tex] into the equation:
[tex]\[ (-7+7)^2 + (-3-10)^2 = 13^2 \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ (0)^2 + (-13)^2 = 169 \][/tex]
Now, calculate the squares:
[tex]\[ 0 + 169 = 169 \][/tex]
Since [tex]\( 169 = 169 \)[/tex], point [tex]\((-7, -3)\)[/tex] lies on the circle.
### Analyzing Option C: [tex]\((-6, -10)\)[/tex]
Substitute [tex]\( x = -6 \)[/tex] and [tex]\( y = -10 \)[/tex] into the equation:
[tex]\[ (-6+7)^2 + (-10-10)^2 = 13^2 \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ (1)^2 + (-20)^2 = 169 \][/tex]
Now, calculate the squares:
[tex]\[ 1 + 400 = 401 \][/tex]
Since [tex]\( 401 \neq 169 \)[/tex], point [tex]\((-6, -10)\)[/tex] does not lie on the circle.
### Analyzing Option D: [tex]\((6, 23)\)[/tex]
Substitute [tex]\( x = 6 \)[/tex] and [tex]\( y = 23 \)[/tex] into the equation:
[tex]\[ (6+7)^2 + (23-10)^2 = 13^2 \][/tex]
Simplify the expression inside the parentheses:
[tex]\[ (13)^2 + (13)^2 = 169 \][/tex]
Now, calculate the squares:
[tex]\[ 169 + 169 = 338 \][/tex]
Since [tex]\( 338 \neq 169 \)[/tex], point [tex]\((6, 23)\)[/tex] does not lie on the circle.
### Conclusion:
The point that lies on the circle represented by the equation [tex]\((x+7)^2 + (y-10)^2 = 13^2\)[/tex] is:
B. [tex]\((-7, -3)\)[/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.